Suppressing Electromagnetic Radiation by Trapping Ferrite Nanoparticles and Carbon Nanotubes in Hierarchical Nanoporous Structures Designed by Crystallization‐Induced Phase Separation. Issue 4 (29th January 2018) - Sharma, Maya; Singh, Deepinder; Menon, Aishwarya; Madras, Giridhar; Bose, Suryasarathi
Abstract: Polymer blends are at the forefront of research especially in the field of Electromagnetic Interference (EMI) shielding because of their versatile properties such as ease of processability, economic viability and high strength to weight ratio. Herein, we have attempted to design lightweight blend composites consisting of multiwalled carbon nanotubes (MWNTs) and nickel ferrite (NiFe2 O4 ) nanoparticles. A unique approach was adopted here to prepare ultra‐thin (500 μm), flexible, lightweight composite membranes wherein hierarchical nanoporous structures were initially developed by crystallization induced phase separation in a classical upper critical solution temperature (UCST) pair Polyvinylidene fluoride/poly methyl methacrylate (PVDF/PMMA) and subsequently etching out the PMMA phase. In the next step, functional nanoparticles were trapped in the pores by facile vacuum filtration approach. This unique approach led to the fabrication of nanoporous composite membranes which otherwise is difficult to process using conventional techniques. The composite membranes show high magnetic permeability and high electrical conductivity; the two key requirements for effective shielding of electromagnetic (EM) radiation. A significant improvement in shielding effectiveness (SE) was achieved using these token composite membranes. For instance, porous PVDF composite membranes containing 3 wt % MWNTs (with a thickness of 500 μm) showed an SE of 8 dB which enhanced significantly to 27 dB for composite membranes wherein NiFe2 O4 is trapped in the pores. More interestingly, the mechanism of shielding was driven by absorption (nearly 80%) through synergistic properties of interconnected MWNTs and NiFe2 O4 nanoparticles. Abstract : Ultra‐thin (500 μm), flexible, lightweight composite membranes with hierarchical nanoporous structures developed using crystallization induced phase separation of PVDF/PMMA blends with trapped MWNTs and NiFe2 O4 nanoparticles in the pores showed a high SE of 27 dB.